La inconveniencia del estándar de persona razonable en derecho penal - Pérez-León Acevedo, Juan Pablo (2014)
Following American legal sources, I argue that the use of the reasonable person standard in criminal law is inaccurate and unfair, and, therefore, inconvenient to evaluate human behaviour based on three arguments which address flaws of the standard under analysis. Firstly, this standard is by definition abstract, theoretical and general, not reflecting appropriately the person’s sensory and ideational perception of the situation. Secondly, the trend in American legislation and case-law is to apply, in criminal cases, e.g., self-defence, a hybrid criterion, which consists in the consideration of a person’s belief and the correspondence of such a belief to what a reasonable person would believe under the circumstances, as opposed to a purely objective standard. The principle of individual criminal culpability underlies this. Thirdly, the reasonable person standard imposes a sort of majority’s dictatorship by perpetuating a predominant culture disregarding the viewpoints from minority groups.